2023
DOI: 10.3390/su15031837
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities in the Management of Electronic Waste and Its Impact on Human Health and Environment

Abstract: Electronic waste (e-waste) is the fastest-growing class of waste because of the remarkable demand for various electronic gadgets such as mobiles and laptops. Moreover, its improper disposal is life-threatening because it includes hundreds of different substances, many of which are toxic elements and pollutants that can leach to soil and surface and groundwater or be emitted into the air, causing a major negative impact on the environment and public health. As a result, studies on the sustainable management of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 153 publications
(200 reference statements)
0
10
0
Order By: Relevance
“…Inadequate disposal and repurposing of DEEE can engender the liberation of various injurious substances, thereby exerting deleterious effects on atmospheric, aquatic and terrestrial domains, as well as human well-being [117,118]. Electronic waste harbours dangerous substances and deleterious additives, which, if dispersed via unsuitable handling and disposal methodologies, can present a substantial peril to the quality of the atmosphere [119]. Furthermore, the reclamation activities related to e-waste encompass conveyance, disassembly of materials, incineration, and, notably, the metallurgical extraction of constituents such as Au and Cu from DEEE.…”
Section: Environmental and Health Effects Of Some Toxic Substances Pr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Inadequate disposal and repurposing of DEEE can engender the liberation of various injurious substances, thereby exerting deleterious effects on atmospheric, aquatic and terrestrial domains, as well as human well-being [117,118]. Electronic waste harbours dangerous substances and deleterious additives, which, if dispersed via unsuitable handling and disposal methodologies, can present a substantial peril to the quality of the atmosphere [119]. Furthermore, the reclamation activities related to e-waste encompass conveyance, disassembly of materials, incineration, and, notably, the metallurgical extraction of constituents such as Au and Cu from DEEE.…”
Section: Environmental and Health Effects Of Some Toxic Substances Pr...mentioning
confidence: 99%
“…Furthermore, e-waste is predominantly discarded and exported from developed nations to developing nations in Asia, Africa, the Middle East, etc. Reports have demonstrated that roughly 12.5% of such waste undergoes rudimentary recycling methods, leading to the release of toxic substances into the ecosystem [119]. Beyond persistent organic pollutants, a multitude of heavy metals pervade the groundwater and rivers of developing countries and render their water unsuitable for consumption and culinary use [124].…”
Section: Environmental and Health Effects Of Some Toxic Substances Pr...mentioning
confidence: 99%
“…Overall, and as summarized in Figure 3, there are different possible routes for the utilization of paper waste to return its value to the economy and reduce its environmental impact. It is important to mention that some of these routes are also used for the utilization of other kinds of waste, such as electronic waste [189,190]. The greenness and efficiency of the conversion of paper waste into energy are significantly dependent on the form of energy (biofuel, biogas, hydrochar, or heat), the conversion method (SSF, carbonization, anaerobic digestion, or incineration), and the used processing conditions (temperature and others).…”
Section: Soil Amendment By Compostingmentioning
confidence: 99%
“…In developing countries, most waste is composed of organic materials, which are generally three times higher than in industrialized countries [2]. The improper disposal of electronic waste, polythene materials, and medical waste in the locality also contributes to pollution and public health hazards [3][4][5]. Waste management (WM) involves several interdependent activities such as collection, source separation, storage, recycling and reuse, biological treatment, transportation etc.…”
Section: Introductionmentioning
confidence: 99%